2020
DOI: 10.3390/ijms21249623
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Comprehensive Investigations of Pyrrolo[3,4-d]pyridazinone-Based 1,3,4-Oxadiazole as New Class of Selective COX-2 Inhibitors

Abstract: The long-term use of Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) in treatment of different chronic inflammatory disorders is strongly restricted by their serious gastrointestinal adverse effects. Therefore, there is still an urgent need to search for new, safe, and efficient anti-inflammatory agents. Previously, we have reported the Mannich base-type derivatives of pyrrolo[3,4-d]pyridazinone which strongly inhibit cyclooxygenase, have better affinity to COX-2 isoenzyme and exert promising anti-oxidant activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…It was found that the structural elements: the heterocyclic moiety, the hydroxyalkyl linker and the 4-substituted piperazine determine the high activity and affinity for 5-HT 1AR receptors [ 12 ]. The significant reactivity of the acid proton at the imide nitrogen atom allows for the preparation of many phthalimide derivatives, and the type of pharmacophore introduced into the molecule determines the direction of action of the new derivatives [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the structural elements: the heterocyclic moiety, the hydroxyalkyl linker and the 4-substituted piperazine determine the high activity and affinity for 5-HT 1AR receptors [ 12 ]. The significant reactivity of the acid proton at the imide nitrogen atom allows for the preparation of many phthalimide derivatives, and the type of pharmacophore introduced into the molecule determines the direction of action of the new derivatives [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the first step, we conducted the formation of Mannich base type derivatives 2a, b-4a, b through one-step reaction of 1a, b with appropriate disubstituted 4phenylpiperazine and 37% solution of formaldehyde in anhydrous ethanol, as it has already been described [32]. Subsequently, in order to achieve structures 5a, b-7a, b, the reaction of 1a, b was carried out in ethanol, alongside with the presence of sodium ethoxide and suitable 1-(2-chloro-1-oxoethyl)-4-disubstituted phenylpiperazine, as described in our earlier paper [31]. The formed precipitates were filtered off, washed with ethanol and purified by crystallization from this solvent.…”
Section: Chemistrymentioning
confidence: 99%
“…In our previous paper, we have reported the synthesis of 1,3,4-oxadiazole based derivatives of pyrrolo [3,4-d]pyridazinone [31,32]. Introduction of 1,3,4-oxadiazole moiety to the pyrrolo [3,4-d]pyridazinone core was aimed to improve COX-2 affinity and reduce gastrotoxicity of investigated structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1,3,4-oxadiazole motif was inserted into two new classes of hybrid compounds, with anti-inflammatory activity, that exert selective COX-2 inhibition [ 1 , 2 ]. This oxadiazole isomer was also included in the structure of indole hybrid able to target Bcl-2, with in vitro pro-apoptotic activity [ 3 ].…”
mentioning
confidence: 99%